Profile of diabetes in men aged 79–97 years: the Western Australian Health in Men Study - Henze, M.; Alfonso, Helman; Flicker, L.; George, J.; Chubb, S.; Hankey, G.; Almeida, O.; Golledge, J.; Norman, P.; Yeap, B. (Wiley-Blackwell Publishing Ltd., 2017)
© 2016 Diabetes UK Aims: To investigate behavioural, physical and biochemical characteristics associated with diabetes in the oldest age group of elderly men. Methods: We conducted a cross-sectional analysis of community-dwelling men aged 79–97 years from Perth, Western Australia. Lifestyle behaviours, self-rated health, physical function, and fasting glucose and HbA 1c levels were assessed. Results: Of 1426 men, 315 had diabetes (22%). Men with diabetes were of similar age to men without (84.9 vs 84.5 years; P = 0.14). Only 26.5% of men with diabetes self-rated their health as excellent or very good, compared with 40.6% of men without diabetes (P < 0.001). Diabetes was associated with less involvement with recreational walking (32.7 vs 41.0%; P < 0.01) and leisure activities (19.0 vs 26.5%; P < 0.01). Men with diabetes had poorer physical function on multiple measures, including longer times for the Timed Up-and-Go test (15.0 ± 6.9 s vs 13.4 ± 5.3 s; P < 0.001) and weaker knee extension (20.2 vs 21.9 kg; P < 0.001). In multivariate analyses, diabetes was associated with an increased prevalence of myocardial infarction (odds ratio 1.80, 95% CI 1.25–2.60; P < 0.001) and falls resulting in injury (odds ratio 1.55, 95% CI 1.06–2.26; P = 0.02). Average HbA 1c was 49 ± 8 mmol/mol (6.6 ± 0.8%) in men with diabetes, with 90.6% of these men on diet or oral hypoglycaemic therapy. Conclusions: In older men, diabetes is associated with poorer self-perceived health, reduced healthy lifestyle behaviours and physical function, heart disease and injurious falls. The majority of these men with diabetes had good glycaemic control. Encouraging healthy lifestyle behaviours and improving physical function should be evaluated as interventions to improve quality-of-life and health outcomes.